Advanced JavaScript: Speed up Web Development with the Powerful Features and Benefits of JavaScript - Shute, Zachary (Packt Publishing, Limited, 2019)
Advanced JavaScript is a hands-on book that takes you through JavaScript and its many features, one step at a time. You'll begin by learning how to write JavaScript in a professional environment using the new JavaScript syntax in ES6. You'll discover how you can leverage the asynchronous nature of JavaScript using callbacks and promises, and.